Travail d’organisation gestionnaire des cadres et mutation des entreprises publiques - Valérie Boussard (La Nouvelle Revue du Travail)
The paper questions the role managers play in transforming state-owned enterprises, notably by shaping them along neo-liberal lines. It highlights the fact that changes in organizational modes and practices are largely driven by the activities of certain managers who view their profession as consisting of “organizing work”. They use this conception to legitimate their ambition of holding executive and managing positions in firms. Findings are based on a recent survey using a sample comprised of managers from a large French state-owned enterprise.